Stochastic differential and difference equations / Imre Csiszár, György Michaletzky [editors] - Csiszár, Imre editors
This volume contains a selection of papers presented at the Conference on Stochastic Differential and Difference Equations held in Hungary, August 1996. The papers cover a wide range of contemporary topics in stochastics with particular reference to control theory.